Large-scale ﬂuctuations and particle diffusion across external magnetic ﬁeld in turbulent plasmas - Zagorodny, A.; Holod, I. (Condensed Matter Physics, 2000)
Kinetic theory of electromagnetic ﬂuctuations in turbulent plasmas in the
external magnetic ﬁeld has been worked out with regard for the effect of
ﬂuid-like random motions on ﬂuctuation dynamics. The dielectric response
functions and correlation functions of the Langevin sources for the system under consideration are calculated and general relations for ﬂuctuation spectra are derived. Fluctuations associated with the diffusive particle
motion across the external magnetic ﬁeld are studied in detail. Розроблено кінетичну теорію електромагнітних флуктуацій у турбулентній плазмі за наявності зовнішнього магнітного поля з урахуванням впливу випадкових гідродинамічних рухів на динаміку флуктуацій. Обчислено функції діелектричного відгуку і кореляційні функції ланжевенових джерел та отримано загальні вирази для спектрів
флуктуацій. Детально вивчено флуктуації пов’язані з дифузійним рухом частинок поперек зовнішнього магнітного поля.